The Impact of Learning Strategies, Self-Efficacy Perception, Self-Esteem, Self-Regulation, and Academic Achievement on Academic Motivation among Students at the University of Dhi Qar: The Moderating Role of Gender and the Mediating Role of Psychological Capital - Zaben Khawwaf, Zaman; Mahdad, Ali; Salman Gatfan, Muntadher; Farhadi, Hadi (International Journal of Education and Cognitive Sciences, 2022)
Purpose: The present study aimed to investigate the impact of learning strategies, self-efficacy perception, self-esteem, self-regulation, and academic achievement on academic motivation, considering the moderating role of gender and the mediating role of psychological capital among students. Methods and Materials: The statistical population included all male and female students of the University of Dhi Qar in 2024, from which 300 students (150 females and 150 males) were selected using multistage cluster random sampling. Data were collected through questionnaires on Learning Strategies (Karami et al., 2005), Academic Self-Efficacy (Owen & Framen, 1988), Self-Esteem (Rosenberg, 1965), Self-Regulation (Bouffard, 1995), Psychological Capital (Luthans & Avolio, 2007), Academic Achievement (Pham & Taylor, 1999), and Academic Motivation (Harter, 1981). The data were analyzed using Pearson correlation, stepwise regression, and structural equation modeling (SEM) with SPSS-21 and AMOS-23 software.  Findings: The results indicated that learning strategies, self-efficacy perception, self-esteem, self-regulation, and academic achievement indirectly influenced academic motivation through psychological capital (p < .01). Regarding the moderating role of gender, the findings revealed that gender moderated the relationship between learning strategies and academic motivation (p < .01). Specifically, the relationship between learning strategies and academic motivation was significant among female students but not among male students. However, gender did not moderate the relationship between self-efficacy perception, self-esteem, self-regulation, academic achievement, and academic motivation. Conclusion: These results highlight the importance of psychological capital as a mediating variable between the study variables and its central role in promoting adaptive behaviors in the classroom, which leads to personal growth, helps prevent dropout, increases motivation, enhances academic achievement, and contributes to a more satisfying academic experience.